A critical review of the approaches and attitudes of South African property valuers towards the valuation of hotels under a contemporary management agreement - Godwin, Wayne (Department of Construction Economics and Management, 2018)
This paper looks at the attitudes and approaches of South African property valuers to the valuation of hotels as an asset class. The paper focuses on the impact in a shift towards management agreements in the sector. Management agreements are a relatively new tenure agreement in South Africa's hotel sector, and although these grew in popularity globally in the 1970's and 1980's, the sanctions which prevented multinational companies wanting to do business in South Africa, allowed local hotel groups to grow in the absence of the world's leading lodging companies. South African property valuers were less exposed to the evolving valuation frameworks and best practice approaches, in the absence of these global companies. This study establishes a framework for optimal hotel valuations under a management agreement, with a review of literature discussing the correct approach to valuing a hotel under such an agreement as well as the the current state of the valuation industry in South Africa; as well as areas of weakness that South African valuers have with certain techniques and approaches that are established as important for hotel valuation. The empirical study that was undertaken surveyed members of the South African Institute of Valuers. The findings present the first comprehensive look at valuation of hotels as an asset class in South Africa; and show that almost half of property valuers in South Africa perceive themselves to be competent in valuation hotels under a management agreement whilst perceiving there to not be a significant difference required for the approach to valuing a hotel under a management agreement. The results of a hypothetical case study within the survey presented a divergent view of competency, with low levels of full competency demonstrated. The study brings much needed perspective on the sector at a time where management agreements are becoming more prevalent and investors are looking to valuers for strategic insight and assurance around the asset class.